Uterine microbiota plasticity during the menstrual cycle: Differences between healthy controls and patients with recurrent miscarriage or implantation failure. (June 2022) - Vomstein, Kilian; Reider, Simon; Böttcher, Bettina; Watschinger, Christina; Kyvelidou, Christiana; Tilg, Herbert; Moschen, Alexander R.; Toth, Bettina
Abstract: In contrast to the former notion of a sterile womb, sequencing techniques have proven a bacterial colonization of the uterus. However, timing of microbiota analysis regarding possible intra-cycle variations as well as specific alterations in patients with recurrent miscarriage (RM) or recurrent implantation failure (RIF) remain unknown. In total, n = 20 RM-, n = 20 RIF-patients and n = 10 healthy controls were included in this prospective study. In every subject, uterine flushing was performed during follicular, ovulatory and luteal phase. Bacterial DNA was isolated and 16S amplicon sequencing analysis of the V3-V4 region was carried out. Diversity measures were compared between samples from the disease groups and the control group separately for each timepoint of the menstrual cycle and over time. In the control group a significant decrease of species richness and evenness was shown around ovulation which remained at this lower level during the luteal phase (Shannon index), indicating a more uniform distribution of microbiota (p < 0.05). This loss of diversity during the menstrual cycle was not apparent in RIF and RM patients. A higher similarity was seen in taxonomic distribution between RM and RIF patients compared to the control group. Longitudinal dynamics included increases in Firmicutes (controls and RM only) and a concomitant loss of Proteobacteria in controls that was not present in RIF and RM. We demonstrate longitudinal intra-cycle-dependent changes in the endometrial microbiota of healthy controls. An increased diversity in both patient groups could be the cause or consequence of a micro-environment that is more prone to pregnancy failures. Graphical Abstract: ga1 Highlights: Healthy controls show a more uniform distribution of microbiota around ovulation and luteal phase. This loss of diversity is not apparent in RIF and RM patients. A higher similarity was seen in taxonomic distribution between RM and RIF. A lower abundance of Lactobacillacea indicates an altered microenvironment This microenvironment could make patients more prone to pregnancy failures.